Peranan Home Industry Kerupuk LIA JAYA Terhadap Tingkat Kesejahteraan Masyarakat dalam Perspektif Ekonomi Islam (Studi Kasus: Masyarakat Desa Pasar Pedati, Kecamatan Pondok Kelapa, Bengkulu Tengah) - Dhita Amelia Puspita; Nurul Hak; Nonie Afrianty (Universitas Muhammadiyah Surabaya, 2025)
This study aims to examine the role of the Lia Jaya Crackers Home Industry in improving the welfare of the community of Pasar Pedati Village and to analyze it from the perspective of Islamic economics. Using a descriptive qualitative method through observation, in-depth interviews, and documentation, this research finds that the home industry plays an important role in providing employment opportunities for the community, particularly for women and residents affected by layoffs, thereby helping increase household income, fulfill basic needs, and improve overall quality of life. The home industry also contributes positively to social aspects by enhancing workers’ self-confidence, economic independence, and participation in productive activities, although several limitations remain, such as the absence of health insurance and formal labor protection. From the perspective of Islamic economics, the activities of the Lia Jaya Crackers Home Industry align with the principles of maslahah, justice, lawful work, and community empowerment, as it provides real benefits to society without contradicting Islamic values.